Papel das ROS provenientes de NADPH oxidase na virulência de Staphylococcus aureus in vitro e em modelo de infecção cutânea. - Elias Junior Mota de Oliveira (2024)
The skin is the largest organ in the human body and is the first line of defense against pathogens, functioning as a physical-chemical barrier. Although the skin acts as a protective barrier against external agents, some microorganisms, especially bacteria, can breach this barrier and cause diseases. This collection of diseases is known as skin and soft tissue infections (SSTIs) and is commonly encountered in both outpatient and hospital settings. The incidence of SSTIs has increased over the last two decades, and there are several pathological conditions that predispose individuals to these infections, such as diabetes mellitus. S. aureus is considered one of the primary causes of SSTIs due to its extensive range of virulence factors, including proteases, lipases, DNase, toxins, and superantigens. S. aureus can adapt to various situations in the presence of the immune system and often persists as a chronic infection. Reactive oxygen species (ROS) production is a crucial mechanism of the immune system. However, S. aureus has the ability to survive even in environments rich in ROS, such as wounds in diabetic and obese patients. In light of this, the objective of this study was to evaluate the effect of ROS on the virulence of S. aureus in infection models both in vivo and in vitro. Our results demonstrate that alpha-toxin expression is influenced by the ROS-rich environment within the phagosome. Furthermore, macrophages from animals deficient in Gp91phox showed higher bacterial killing compared to wild-type animals. Additionally, our in vivo data indicate that inhibiting ROS production using apocynin or in Gp91phox-deficient mice leads to reduced wounds and increased clearance of S. aureus. Moreover, treatment with apocynin accelerated the wound healing process. In conclusion, our data suggest that ROS from NOX play an essential role in inducing S. aureus virulence.